KEPERCAYAAN DIRI DAN KECEMASAN KOMUNIKASI INTERPERSONAL PADA MAHASISWA - Siska, -; Sudardjo, -; Purnamaningsih, Esti Hayu (Faculty of Psychology, Universitas Gadjah Mada, 2003)
The main problem in interpersonal communication anxiety is there are feeling of worried another respons or jugdment for her or him about something that sent and how she was send. Dependability for others judgment is one of characteristics from low self confidence. The purpose of the study was to see the relation between self confidence and interpersonal communication anxiety and differences between communication anxiety at male and female students. The subjects of this study were 61 female and 57 male students from Economic Faculty of UKRIM at Yogyakarta. The hypothesis were: 1. There is a negatif correlation between self confidence and interpersonal communication anxiety, 2. There is a difference communications anxiety between male and female studens. The first and the second hypothesis has analysed by Pearson's product moment correlation and by t test respectivelly. Data were gethered by Self confidence scale modification from Lauster (1978) and interpersonal communication anxiety scale modification from Syarani (1995). The result showed there was significant negatif correlation between self confidence and interpersonal communication anxiety (r = - 0,725 ; p < 0,01) and the t test showed a value of r = -0,678 and p > 0.05. From the values above, it could be concluded that there was no differences of interpersonal communication axxiety in male and female students.